The importance of shared understanding within football teams - Malone, M. K.; Lorimer, R. (Journal of Sport Psychology in Action, 2020)
Within a football team, it is vital for coaches to acknowledge the importance of their players having the knowledge of what is required in specific roles in the team and what their other team members are likely to do in certain situations. This mutual knowledge can be defined as shared understanding - the ability for two or more people to have similar thoughts in specific situations based on their experience together. This paper considers what shared understanding is, its importance within team sports like football and the positive implications for teams who have players with accurate shared understanding. This paper provides practical suggestions for how coaches can develop shared understanding within their team.